EXPRESSIVE SPEECH ACTS IN STAND-UP COMEDY BY RADITYA DIKA - Nurpadilah, Sintia Dona; Ningsih, Rahayu; Noerbayani, Pani; Basra, Sri Meiweni (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
This study delved into the realm of expressive speech acts within stand-up comedy, with a specific focus on Raditya Dika's "Cerita Cintaku" YouTube series. Drawing from John Searle's theoretical framework, which encompassed emotion-showing, mood-indicating, aesthetic judgment, and expressive vocabulary, the research explored the intricate dynamics of linguistic choices and audience responses. Employing a qualitative case study approach, two selected videos were analyzed to unravel the nuanced use of expressive speech acts. The findings shed light on Raditya Dika's comedic craft, emphasizing the interplay between expressive speech, emotional expression, and inherent humor. The abstract underscored the specificity of linguistic elements, provided insights into the chosen methodology, and articulated the interface between Searle's theory and the empirical findings. This research contributed to a deeper understanding of the role of expressive speech in stand-up comedy, offering a unique perspective on audience engagement and comedic impact.